2005
DOI: 10.1002/rra.849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dam‐induced flow regime change on downstream river morphology and vegetation cover in the Hwang River, Korea

Abstract: The Hapchon Dam, located in the headwaters of the Hwang River, Korea, was completed in 1988. Due to low storage levels, the spillway has not been operated over the past decade. Thus, a new ecosystem has become established in the river downstream of the dam. This is not a common phenomenon in Korean rivers. This study investigates the effect of flow regime change on the river morphology and vegetation cover in a reach downstream of the dam following its construction. Geomorphological effects shown by pre-and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 10 publications
7
38
0
4
Order By: Relevance
“…However, the reach at the end of the study reach showed channel division into several sub channels and island formation with establishment of perennial vegetation. The increase in vegetated areas and in the areas covered by islands also corroborates the observations of Choi et al (2005). -dam (1989-2005) 126 355.3 3.5…”
Section: Flow Regimesupporting
confidence: 85%
“…However, the reach at the end of the study reach showed channel division into several sub channels and island formation with establishment of perennial vegetation. The increase in vegetated areas and in the areas covered by islands also corroborates the observations of Choi et al (2005). -dam (1989-2005) 126 355.3 3.5…”
Section: Flow Regimesupporting
confidence: 85%
“…Overall, dams and river diversions have proven to be severely detrimental to aquatic habitat, contributing to the destruction of fisheries, extinction of species and the loss of ecosystem services vital to the human economy Rosenberg et al 2000). In particular, the negative impact of flow regulation upon the morphological and successional diversity of flood plains has been highlighted (Ward & Stanford 1995;Gilvear 2004;Hohensinner et al 2004;Choi et al 2005).…”
Section: 1 I M P a C T O F R I V E R M A N A G E M E N T A N D R E mentioning
confidence: 99%
“…Los procesos de erosión, transporte y deposición causan la perturbación y alta heterogeneidad del medio y la comunidad científica ha abordado de manera prolífica el cómo estos flujos de materia y energía entre río -inundaciones-, ribera y ladera incentivan el ciclo de sucesión vegetal y los factores bióticos de repoblación de las especies (Azami et al, 2004;Brinson y Verhoeven, 1999;Brookes et al, 2000;Choi et al, 2005;Gergel et al, 2002;Glenz, 2001;Glenz et al, 2003;McGlynn y Seibert, 2003;Ocampo et al, 2006;Shiau y Wu, 2004;Suzukia et al, 2002;Tabacchi et al, 1998Tabacchi et al, , 2005Wen et al, 2010;Williams et al, 1998, entre otros).…”
Section: Aspectos Introductorios Para La Modelación Ecohidrológica Deunclassified
“…Los ecosistemas forestales de ribera son reguladores de importantes procesos hidrológicos (Lowrance et.al, 1998;Tabacchi et al, 2000). Se tiene por un lado, el clima y el suelo como controladores de la dinámica de la vegetación y por otra parte, la vegetación que ejerce una modulación importante sobre el balance total de agua, lo que a su vez la convierte en responsable, en gran medida, de los mecanismos de retroalimentación entre suelo y atmósfera .Los procesos de erosión, transporte y deposición causan la perturbación y alta heterogeneidad del medio y la comunidad científica ha abordado de manera prolífica el cómo estos flujos de materia y energía entre río -inundaciones-, ribera y ladera incentivan el ciclo de sucesión vegetal y los factores bióticos de repoblación de las especies (Azami et al, 2004; Brinson y Verhoeven, 1999;Brookes et al, 2000;Choi et al, 2005;Gergel et al, 2002;Glenz, 2001;Glenz et al, 2003; McGlynn y Seibert, 2003;Ocampo et al, 2006; Shiau y Wu, 2004;Suzukia et al, 2002;Tabacchi et al, 1998 Tabacchi et al, , 2005 Wen et al, 2010;Williams et al, 1998, entre otros).El régimen hidrológico del río a su vez es responsable del mantenimiento del ecosistema (Naiman et al, 2005) y en riberas con períodos cortos de inundación la sequía puede ser un factor incluso más limitante que la inundación misma (Heller, 1969). Por ello, otra rama importante del estudio de dicho ecosistema enfatiza el conocimiento sobre la disponibilidad del agua en la composición, estructura, distribución, crecimiento y desarrollo de la vegetación de ribera (Baird y Maddock, 2005; Horton y Clark, 2000; Goodwin y Tarboton, 2001;Maddock et al, 1998;Scott et al, 2000;Snyder y Williams, 2000;Stromberg et al, 1993; Webb y Leake, 2006;Williams et al, 1998; entre otros).…”
unclassified
See 1 more Smart Citation